Online Teaching: Challenges Experienced by Students and Teachers during the Covid-19 Pandemic in Kathmandu - Gyawali, Sindhu (International Research Journal of MMC, 2023)
COVID-19 pandemic has entirely put the world upside down and has adversely affected the economy, social life, tourism, education and others all around the globe. As there is a prolonged period of lockdown, there is uncertainty everywhere. The ravaged pandemic has affected the education sector widely. Due to the implementation of social distancing, almost all the universities and colleges throughout the world have been closed and are forced to shut down. Realizing the consequences, countries are internationally adopting a practice of online teaching in the pandemic period. Online learning is in the nascent stage in countries like Nepal. This study aimed to gain insights into pro challenges encountered by teachers and students while transitioning to online learning during the COVID-19 pandemic in higher education. The study is based on an exploratory research design, following both quantitative and qualitative methods. A survey was conducted with a pre-structured questionnaire. Then the standardized open-ended interview was assessed with faculties and students who were engaged in online classes during a pandemic period. This current study concluded that the COVID-19 pandemic should be taken as an opportunity brought by the crisis in the education sector. It was necessary for the Nepalese government and concerned stakeholders in education sector for immediate response so that education would not be in halt. However, there were some common challenges highlighted by participants such as limited electricity and unreliable internet, limited infrastructures and technology, and low digital knowledge and skills of teachers, which hampers the effectiveness of teaching-learning activities.